Aprovechamiento de la especie Lepidocaryum gracile Martius “IRAPAY” en el caserío de San Lucas y su relación al desarrollo sostenible Maynas - Loreto 2022 - Tenorio Pinedo, Leticia Yavilett (2024)
The present study has been carried out in the San Lucas Hamlet located on Iquitos-Nauta km 43 Highway, to determine what is the relationship between the current situation of the utilization of the species (Martius (Irapay) in the forests surrounding the hamlet of San Lucas, what is the relationship between the current situation of the utilization of the species (Lepidocaryum gracile Martius (Irapay) in the forests surrounding the hamlet of San Lucas with the indicators of sustainable development. From the obtained results, it can be seen that the extractors make 2 to 3 monthly visits to the forest for the extraction of leaves, remaining an average of 10 calendar days, managing to extract an average of 40,000 leaves (bones).) placed in your home. The cost of extracting 40,000 leaves (bones) is s/. 1,444.8, equivalent to a value of S/.0.03612 per leaf. The costo f making crisnejas is .2.04 placed at the home of the extractors of San Lucas. The costs of making crisnejas and purchasing axes are the highest with 49% of the total cost each. There is no profit in the sale of loads of a thousand sheets, if it generates a los of 46.94%. If there is profit in the sale of crisnejas, it amounts to 31.73% of the total cost (S/. 3.00). Crisnejas extractors are 100% ilegal. In the ecological aspect we can affirm that there is a serious risk regarding the disappearance of the species, which is moving away from the San Lucas populated center. In the socio-economic aspect, the extractors are approaching the category of extreme poverty since Little by Little thay are losing the resource. According to the statistical análisis, the two variables are related and depending on the treatment.